THE MEANING OF NON - VERBAL COMMUNICATION IN A TECHNOLOGY TEACHER'S WORK - Henryk, NOGA (Trends in education, 2010)
The subject of the analysis is non-verbal communication of a technology teacher. The research show what is the role of non-verbal communication in the work of a technology teacher, particularly what is its influence over the process of remembering by pupils. A very important element of teacher - pupil communication as such is non-verbal communication. It also refers to technology teachers.
Keywords: technology teaching; interpersonal communication